Mediation and governance in fragile contexts small steps to peace - Dekha Ibrahim Abdi 1964-2011; Mason, Simon A. 1971- (Lynne Rienner Publishers, 2019)
Introduces an innovative, practical approach to resolving an enduring issue: How can conflicts be resolved in polarized societies and fragile states?